Do Firms Benefit from Active Labour Market Policies? - Michael Lechner; Conny Wunsch; Patrycja Scioch (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper investigates the link between variation in the supply of workers who participate in specific types of active labour market policies (ALMPs) and firm performance using a new exceptionally informative German employer-employee data base. For identification we exploit that German local employment agencies (LEAs) have a high degree of autonomy in determining their own mix of ALMPs and that firms' hiring regions overlap only imperfectly with the areas of responsibility of the LEAs. Our results indicate that in general firms do not benefit from ALMPs and in some cases may even be harmed by certain programs, in particular by subsidized employment and longer training programs. These findings complement the negative assessment of the cost-effectiveness of ALMPs from the empirical literature on the effects for participants.
Keywords: J68; 330; subsidized employment programs; training programs; regional variation; program evaluation